Analyzing Ethical Practices of Digital Marketing in YARSI Islamic Hospital - Nastain Mohammad Dunda; Edi Prasetyo; Enrico Adhitya Rinaldi; Dicky Budiman; Wahyu Sulistiadi (International Journal of Advanced Health Science and Technology, 2025)
The rapid growth of digital technology has transformed healthcare marketing in Indonesia, creating both opportunities and ethical challenges for Islamic hospitals that must uphold Sharia principles. Despite the existence of Sharia certification frameworks, the operationalization of ethical digital marketing in these institutions often remains normative, lacking detailed guidelines and systematic oversight. This study aimed to analyze the ethical implementation of digital marketing at YARSI Sharia Hospital by examining its regulatory framework, implementation process, and compliance mechanisms. A qualitative descriptive–exploratory case study design was applied, involving purposive sampling of key stakeholders including hospital management, the Sharia Ethics Committee, marketing personnel, and patients. Data were collected through semi-structured interviews, direct observation, and document analysis, followed by thematic analysis using Braun and Clarke’s framework and a complementary SWOT assessment. The findings revealed that while YARSI Sharia Hospital possesses formal Sharia certification and governance under a Supervisory Board (DPS), its digital marketing practices are constrained by insufficient human resources, limited Sharia-based training, and the absence of structured audit procedures. Approximately 65% of reviewed content adhered to Sharia ethical principles, while 35% required modification or revision. Nevertheless, the hospital benefits from leadership commitment and a supportive external environment favoring Sharia-compliant healthcare. In conclusion, although YARSI Sharia Hospital demonstrates strategic readiness for ethical and Sharia-based digital marketing, improvements are needed in capacity building, the establishment of platform-specific ethical regulations, and the institutionalization of periodic compliance audits to ensure sustainable ethical performance and competitive advantage in Islamic healthcare services.